A study on factors that influence the performance of Sukuk in Malaysia / Nur Fatin Ibrahim - Ibrahim, Nur Fatin (2013)
The development of sukuk has been growing so fast since the first issuance in Malaysia in the early 1990 which known as Islamic Private Debt Securities (IPDS) and becoming more popular among Muslim and non-Muslim consumers. The aim of this study is to analyze the factors that influence performance of Sukuk in Malaysia. The study were used a quantitative method which based on secondary data that could be collected from Central Bank Report, Securities Commission Report, Islamic Bond Market Report, etc. Moreover, the data were collected over the five-year period starting from January 2005 up to December 2009 by using the regression model. The findings of the study are interest rate, inflation rate, Gross Domestic Product (GDP) and stock index which could be the factors or variables that can influence performance of Sukuk in Malaysia. Constraints found in the study due to lack of availability data, references. It is hoped that this study will benefit for references to the future since there are a few researcher have done on the topic of Sukuk in Malaysia especially for those who intended to do the same research.